SYNTHESIS, CHARACTERIZATION AND ANTIBACTERIAL PROPERTIES OF SOME HETEROLEPTIC METAL(II) COMPLEXES OF PARACETAMOL AND VANILLIN - A Osowole, Aderoju; Agbaje, Oluwatoosin B. A.; O. Ojo, Babatope (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: This study was aimed at investigating the suitability of Paracetamol and Vanillin in forming low spin, novel heteroleptic, octahedral metal(II) complexes and the potentials of the metal(II) complexes as broad-spectrum antibacterial agents in-vitro. Methods: Heteroleptic metal(II) complexes of Paracetamol (HL) and Vanillin(HL1) were synthesized and characterized by percentage metal analysis, infrared and electronic spectroscopies, room temperature magnetic moments, melting points, conductance measurements. The antibacterial activity of the synthesized complexes as well as their metal-free ligands was studied using the agar diffusion technique. Results: Infrared spectra data confirmed that coordination was via the Paracetamol and Vanillin phenol and carbonyl oxygen atoms. The room temperature magnetic moment and electronic spectra data indicated that all the metal(II) complexes assumed octahedral geometry. Furthermore, the Ni(II) complex showed high spin Â low spin octahedral equilibrium, and the Cu(II) complex was dimeric and antiferromagnetic.Â The molar conductances of the metal(II) complexes in DMSO showed that the complexes were covalent. Interestingly, the in-vitro antibacterial studies on these metal(II) complexes, Paracetamol and Vanillin against Bacillus cereus, Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Klebsiella oxytoca and Staphylococcus aureus showed that the Cobalt(II) complex had the best antibacterial activity, being active against all the bacteria used with inhibitory zones range of 19.0-26.0 mm proving it’s potentials as a broad spectrum antibacterial agent. Conclusion: Infrared and electronic spectroscopies, with room temperature magnetic moments indicated a monomeric, 6-coordinate octahedral geometry for all the complexes with the exception of the Cu(II) complex, which was dimeric. Â Keywords: antibacterial, covalent, equilibrium, paracetamol, vanillin